GESTÃO DO CONHECIMENTO PARA TOMADA DE DECISÃO: UM ESTUDO DE CASO NA EMPRESA JÚNIOR - Thiago Gonçalves Magalhães (Universidade Federal de Santa Catarina, 2014)
Knowledge is the primary resource for organizations in the process of decision making today, in this way, knowledge management is an important tool for the creation and retention of knowledge in organizations, essential to support the decision making process. However the vast majority of companies, especially small and medium still do not have a management process knowledge formalized, but have some practices that also support a positive decision-making. The Ação Júnior Consultorias Socioeconômicas, Junior Enterprise in the CSE- UFSC doesn’t have a structured process of knowledge management, but has several practices in which it subsidizes the executive directors for decision making in the company, thus the aim of the study was ascertain how the practices of knowledge management in the company supports the decision making process. The research is characterized as qualitative, descriptive and applied. Interviews were conducted with members of the executive board in order to raise the practices of knowledge management and further understand how subsidize the process of decision making. As a result one can see that the company has several knowledge management practices, which are of great importance to the decision-making process, however it needs a better structure, formalization and monitoring of such practices and the treatment of the knowledge generated by them.